Conversão de registros de representação: desenvolvimento de aplicativos para o ensino-aprendizagem de funções - Silva, Cíntia Rosa da (2009)
In this work, based on the concept of conversion of registers of semiotic representation, two computer applications for teaching and learning of mathematical functions are developed, and a first version of these applications are tested with undergraduate students. To give account of these objectives, first, this dissertation discusses semiotic representation and registers of representation (DUVAL, 1993), highlighting the concepts of formation of identifiable representation, treatment and conversion. Next, based on the concepts of didactic and informatics transposition, the two applications are described: the first of them, instructional, and the second, functional, the ApliRFunction 1.0. Finally, an exploratory testing with Mathematics undergraduate students at the University of Southern Santa Catarina – Unisul is analyzed. The results, despite extrinsic and intervenient variables, pointing to discrete improvements in the students’ post-test performance, and suggest a set of upgrades for the applications